Posaconazole as part of the antifungal armamentarium in the intensive care unit - case reports from a surgical ICU - Störzinger, Dominic; Lichtenstern, Christoph; Weigand, Markus A.; Hoppe-Tichy, Torsten (Mycoses, 2011)
The authors describe two cases of successful and safe posaconazole use in patients of a surgical intensive care unit of a university hospital.